Design, Formulation, and Characterization of Valsartan Nanoethosomes for Improving Their Bioavailability - Ali M. Nasr; Fayrouz Moftah; Mohammed A. S. Abourehab; Shadeed Gad (MDPI AG, 2022)
The objective of this study was to formulate and evaluate valsartan (VLT) ethosomes to prepare an optimized formula of VLT-entrapped ethosomes that could be incorporated into a sustained release transdermal gel dosage form. The formulation of the prepared ethosomal gel was investigated and subjected to in vitro drug release studies, ex vivo test, and in vivo studies to assess the effectiveness of ethosomal formulation in enhancing the bioavailability of VLT as a poorly soluble drug and in controlling its release from the transdermal gel dosage form. The acquired results are as follows: Dependent responses were particle size, polydispersity index, zeta potential, and entrapment efficiency. The optimized VLT-ETHs had a nanometric diameter (45.8 ± 0.5 nm), a negative surface charge (−51.4 ± 6.3 mV), and a high drug encapsulation (94.24 ± 0.2). The prepared VLT ethosomal gel (VLT-ethogel) showed a high peak plasma concentration and enhanced bioavailability in rats compared with the oral solution of valsartan presented in the higher AUC (0-∞). The AUC (0-∞) with oral treatment was 7.0 ± 2.94 (μg.h/mL), but the AUC (0-∞) with topical application of the VAL nanoethosomal gel was 137.2 ± 49.88 (μg.h/mL), providing the sustained release pattern of VLT from the tested ethosomal gel.